The impact of PKR activation: from neurodegeneration to cancer. Issue 5 (12th February 2014) - Marchal, Juan A.; Lopez, Gabriel J.; Peran, Macarena; Comino, Ana; Delgado, Juan R.; García‐García, Javier A.; Conde, Veronica; Aranda, Fernando M.; Rivas, Carmen; Esteban, Mariano; Garcia, Maria A.
ABSTRACT: An inverse association between cancer and neurodegeneration is plausible because these biological processes share several genes and signaling pathways. Whereas uncontrolled cell proliferation and decreased apoptotic cell death governs cancer, excessive apoptosis contributes to neurodegeneration. Protein kinase R (PKR), an interferon‐inducible double‐stranded RNA protein kinase, is involved in both diseases. PKR activation blocks global protein synthesis through eIF2α phosphorylation, leading to cell death in response to a variety of cellular stresses. However, PKR also has the dual role of activating the nuclear factor κ‐B pathway, promoting cell proliferation. Whereas PKR is recognized for its negative effects on neurodegenerative diseases, in part, inducing high level of apoptosis, the role of PKR activation in cancer remains controversial. In general, PKR is considered to have a tumor suppressor function, and some clinical data show a correlation between suppressed or inactivated PKR and a poor prognosis for several cancers. However, other studies show high PKR expression and activation levels in various cancers, suggesting that PKR might contribute to neoplastic progression. Understanding the cellular factors and signals involved in the regulation of PKR in these age‐related diseases is relevant and may have important clinical implications. The present review highlights the current knowledge on the role of PKR in neurodegeneration and cancer, with special emphasis on its regulation and clinical implications.—Marchal, J. A., Lopez, G. J., Peran, M., Comino, A., Delgado, J. R., García‐García, J. A., Conde, V., Aranda, F. M., Rivas, C., Esteban, M., Garcia, M. A. The impact of PKR activation: from neurodegeneration to cancer. FASEB J . 28, 1965–1974 (2014). www.fasebj.org